Moral Judgment and Empathic/Deontological Guilt. Issue 4 (August 2019) - Migliore, Simone; D'Aurizio, Giulia; Parisi, Francesca; Maffi, Sabrina; Squitieri, Barbara; Curcio, Giuseppe; Mancini, Francesco
Background: People often make complicated decisions to help or to punish perfect strangers. Harming someone or breaking some moral imperative is usually linked to feeling guilt, and several researches suggested the existence of two different kinds of guilt: altruistic/empathic and deontological. Aim: Our study aimed to investigate the decision-making processes in moral and nonmoral judgments and assess how specific situations in which the subject is close to the victim or flanked by an authority can influence his decisions. Methods: We used three different moral conditions: Empathic Moral (the decision has made while physically close to the potential victims), Deontological Moral (the decision has made while flanked by an "authority"), and Standard Moral (without any influence); a fourth condition is represented by Nonmoral dilemmas (the subject must make a choice between two different things and this does not cause any harm or victims). Previously, a pilot study was carried out for validating the experimental stories to be used in the main study. Results: We observed a higher number of utilitarian/positive responses when individuals had to respond to Empathic Moral condition, with respect to Deontological Moral and Nonmoral dilemmas. Moreover, looking at the time needed to read the dilemma, under empathic guilt condition, people tended to be slower in reading the dilemmas than in other conditions and this both in case of positive and negative responses. No significant differences in time needed to effectively respond emerged. Conclusions: These findings suggested that be physically close to potential victims or be flanked by an "authority" differentially influence the decision-making processes in moral judgment, inducing slower decisions and more utilitarian answers, particularly in the scenario of physical proximity.